National guidelines for the management of diabetes mellitus: a nursing perspective - Coleen O'Brien; Dalena van Rooyen; Sheree Carlson (AOSIS, 2006)
Since 1994, the emphasis in the provision of health services in South Africa has shifted from hospital-based care to a community-based comprehensive primary health care system, especially important in the management of chronic diseases, such as Diabetes Mellitus (DM). Opsomming Vanaf 1994 het die klem ten opsigte van die voorsiening van gesondheidsdienste in Suid-Afrika verskuif van hospitaal- gebaseerde gesondheidsorg na 'n gemeenskapsgebaseerde omvattende primêre gesondheidsorgsisteem, veral wat die hantering van chroniese siektes soos Diabetes Mellitus (DM) betref. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.